Thinking outside of the box: Determining students' level of critical thinking skills in teaching and learning / Afifah Fadhlullah and Nurbarirah Ahmad - Fadhlullah, Afifah; Ahmad, Nurbarirah (Penerbit UiTM (UiTM Press), 2017)
This paper discusses the level of critical thinking skills adapted from The Cornell Critical Thinking Test Level X (CCTTX) by Ennis and Milan (1985) among final year diploma students from the Faculty of Business Management, UiTM Melaka taking the course of Office Administration and Introduction to Critical Thinking. This paper aims to encourage students to become critical thinkers and to provide lecturers with the best approach to develop students' critical thinking skills at tertiary level. Findings have shown that their critical thinking ability ranged from low to moderate level. Thus, strategies of teaching and learning which stresses on student-centered learning must be adopted to stimulate student's thinking by encouraging critical and creative thinking and the construction of new knowledge. 61 students taking Diploma in Office Management and Technology were chosen as samples of this study. The data was collected through observation and classroom based activities namely debates, discussions, article analysis, problem-solving situations and case studies.